2018
DOI: 10.1016/j.jaap.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Fast pyrolysis of tannins from pine bark as a renewable source of catechols

Abstract: Fast pyrolysis of water-insoluble (W-I) tannins-mainly composed of condensed tannins-obtained from Pinus radiata bark methanol-water extraction was carried out in pursuit of a renewable source of high-value chemicals, in particular catechols. Micropyrolysis in an isothermal furnace unit (Py-GC-MS/FID) was performed between 450-600°C. Catechin and W-I tannins were compared to establish thermal degradation behavior between this fraction and its representative monomer constituent. Additionally, W-I tannins were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The 723.1cm −1 as C–H bonds indicates the presence of another group of aromatic compounds considering the band between 785–540cm −1 of the C–H stretch group. Majority of the functional groups have been identified by researchers working with other woody biomass classes (Kumar et al., 2010; Pinto et al., 2018; Ogunsanwo et al, 2014) and their classifications are similar to those reported in this study.…”
Section: Resultssupporting
confidence: 86%
“…The 723.1cm −1 as C–H bonds indicates the presence of another group of aromatic compounds considering the band between 785–540cm −1 of the C–H stretch group. Majority of the functional groups have been identified by researchers working with other woody biomass classes (Kumar et al., 2010; Pinto et al., 2018; Ogunsanwo et al, 2014) and their classifications are similar to those reported in this study.…”
Section: Resultssupporting
confidence: 86%
“…It was previously reported by Yang et al (2007) that cellulose pyrolysis occurs in a higher temperature range than lignin and hemicelluloses, and lignin is the most difficult polymer to decompose with a solid residue of 45.7 wt.% [44]. As shown in Figure 4b and Table 2, decomposition of bark (Tonset) initiated at 219 °C and reached a maximum mass loss (Tmax1) at 361 °C, thus representing typical pyrolysis of lignocellulosic material [45,46]. The respective Tonset of PLB and purified PLB were, respectively, 152 and 148 °C and were both lower than that of bark.…”
Section: Characterization Of Bark and Solid Residues Of Plbmentioning
confidence: 71%
“…Therefore, researchers have focused their work on improving the flavonoid recovery methods of some barks, especially when highly lignified barks are wasted from the forestry industry. Recent work has mentioned the extraction of flavonoids from the bark of Pinus radiata [ 24 ], chestnuts species [ 25 ], Caesalpinia ferrea C. [ 26 ], Pinus halepensis [ 27 ], Quercus laurina , Quercus crassifolia , and Quercus scytophylla [ 28 ].…”
Section: Natural Sources Of Flavonoidsmentioning
confidence: 99%